Low-dose chlorine exposure impairs lung function, inflammation and oxidative stress in mice - de Genaro I.S. (2021)
© 2020 Elsevier Inc.Aim: To explore the different consequences of acute and chronic exposure to chlorine gas (Cl2) on the functional and histological parameters of health mice. Main methods: Firstly, male BALB/c mice were acute exposed to 3.3 or 33.3 or 70.5 mg/m3 Cl2. We analyzed the lung function, the inflammatory cells in the bronchoalveolar lavage, cell influx in the peribrochoalveolar space and mucus production. In a second phase, mice were chronic exposed to 70.5 mg/m3 Cl2. Besides the first phase analyses, we also evaluated the epithelial cells thickness, collagen deposition in the airways, immunohistochemistry stain for IL-1β, iNOS, IL-17 and ROCK-2 and the levels of IL-5, IL-13, IL-17, IL-1β and TNF-α in lung homogenate. Key findings: Acute exposure to chlorine impaired the lung function, increased the number of inflammatory cells in the BALF and in the airways, also increased the mucus production. Furthermore, when chlorine was exposed chronically, increased the airway remodeling with collagen deposition and epithelial cells thickness, positive cells for IL-1β, iNOS, IL-17 in the airways and in the alveolar walls and ROCK-2 in the alveolar walls, lung inflammation with increased levels of IL-5, IL-13, IL-1β and TNF-α in the lung homogenate, and also, induced the acid mucus production by the nasal epithelium. Significance: Acute and chronic exposure to low dose of chlorine gas worsens lung function, induces oxidative stress activation and mucus production and contributes to augmenting inflammation in health mice.